Collection of Manuscripts From Malacca Kept in London with Special Emphasis on Adat Raja-Raja Melayu: (Koleksi Manuskrip Melaka di London dengan Tumpuan Khusus terhadap Adat Raja-raja Melayu) (Malay Literature, 2018)
The real situation of the manuscripts originating from the state of Malacca is still a big question. There is no arrangement in a proper listing and is still vaguely understood by society at large. The manuscripts of major works revolving around the history of the Malacca Sultanate are mostly found in other countries, in particular London and Leiden. The splendour of the Malay Sultanate in Malacca during the 15th century seems to have left little impact on the history of Malay manuscript writing. This state of affairs leaves a gap in the history of Malay literature in Malacca as this should have been the earliest location of the Malay manuscript writing tradition. This article will discuss again this issue by conducting an initial study of the collection of manuscripts from Malacca kept in London with special emphasis on the manuscript Adat Raja-raja Melayu.Keywords: Adat Raja-raja Melayu, Malay manuscript, Malacca Sultanate, London, Leiden